Selection of Entry Mode into a Foreign Market: The Cases of U.S. Firms in China - Lee, Han Ping (2010)
Today we see it as natural that companies gradual internationalize to gain success and increase the growth and profit. As internationalisation, they become ever more important for individual business to keep up with the development. Every movement there is reason behind. They do this because they have motivations to do so or they must to do so in order to be competitive on the ever changing market nowadays. Selecting the right entry mode expanding to other countries is an important decision that demands a lot of resources and through proper scheduling. However, they are wide range of internal and external factors influence firm’s choice of international market entry. Enter the right market with appropriate entry mode it might be victorious; the consequences of the entry mode choice can have strong effects on the success of the firm. The study empirically validates the theory in the specific situation of U.S firms in same sector made their presence into China market, which kind of entry modes they went for; further how their market’s entry is influenced by underlying factors. Two qualitative case studies of two U.S MNEs namely Intel and IBM were undertaken. A literature review was conducted, which resulted in a conceptual framework that presented what would guide the data collection.